2021
DOI: 10.1016/j.jvs.2021.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare disparities in vascular surgery: A critical review

Abstract: Health disparities in vascular surgical care have existed for decades. Persons categorized as Black undergo a nearly twofold greater risk-adjusted rate of leg amputations. Persons categorized as Black, Latinx, and women have hemodialysis initiated via autogenous fistula less often than male persons categorized as White. Persons categorized as Black, Latino, Latina, or Latinx, and women are less likely to undergo carotid endarterectomy for symptomatic carotid stenosis and repair of abdominal aortic aneurysms. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…One study found that men were more likely to have AVF 26 compared to women who had less AVF use, 29,43,67 more central venous catheter use, 25,45 less dialysis access patency, 68 and more fistula maintenance interventions 69 . Men were less likely to start dialysis at home, 39 less likely to withdraw from dialysis, 57 had greater kidney function recovery, 70 and go on palliative care more often 42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study found that men were more likely to have AVF 26 compared to women who had less AVF use, 29,43,67 more central venous catheter use, 25,45 less dialysis access patency, 68 and more fistula maintenance interventions 69 . Men were less likely to start dialysis at home, 39 less likely to withdraw from dialysis, 57 had greater kidney function recovery, 70 and go on palliative care more often 42 .…”
Section: Resultsmentioning
confidence: 99%
“…marginalized groups to have lower mortality than white patients (Table 2). Historically marginalized groups received arteriovenous fistulas (AVF), [25][26][27][28][29][30] peritoneal dialysis (PD), [31][32][33][34][35][36][37] home hemodialysis, 31,32,[36][37][38][39] hospice, 40,41 and palliative care 42 less frequently than white patients and were more likely to receive arteriovenous grafts (AVG) 43,44 and central venous catheters. 25,44,45 According to Yap et al, race was not a predictor for PD.…”
Section: Race/ethnicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In vascular medicine, persons categorized as Black with peripheral artery disease have a nearly twofold rate of leg amputation, mainly due to underutilization of screening procedures. 13 The decline in deaths Diversity, Equity, and Inclusion Task Force initiatives within the Society for Vascular Medicine: Current status and future challenges Carmel Celestin 1 , Rafael S Cires-Drouet 2 and Olusegun Osinbowale 3 from cardiovascular disease is not seen equitably across racial and ethnic groups despite controlling for socioeconomic status. 14 White patients have higher rates of coronary artery revascularization compared with Black patients.…”
mentioning
confidence: 99%